IDENTIFIKASI ZONA KERENTANAN PENGGUNAAN LAHAN TERHADAP BENCANA TSUNAMI DI KABUPATEN BANYUWANGI - Maria Christina Endarwati; Widiyanto Hari Subagyo Widodo; Annisa Hamidah Imaduddina (Republic of Indonesia Defense University, 2021)
In a disaster study, the main thing that needs to be done is an assessment related to disaster vulnerability. The 1994 tsunami in the southern coastal area of East Java resulted in 377 deaths, 15 missing people, and 789 injured people. Therefore, identification of land use vulnerability zones in the area needs to be done as a non-structural mitigation effort. The identification of vulnerability zones can be carried out in two stages of analysis, namely AHP analysis and GIS analysis. Based on the results of the analysis, the highest high vulnerability is located in the District of Tegaldlimo with an area of 10,664.99 hectares. Meanwhile, for high vulnerability with the smallest area, it is located in Giri District with an area of 570.29 hectares. Meanwhile, the widest area of vulnerability is in Tegaldlimo District, with a land area of 32,470.20 hectares with a low vulnerability classification.